The emperor and the assassin - Kaige, Chen; Iseki, Satoru; Kaige, Chen (Beijing : Beijing Fil Studio [production company] ; Klang : Multimedia Entertainment [distributor])
A visually stunning epic exploring the devastating price one country pays for peace and one man pays for power. Ying Zheng, the King of Qin, has one driving ambition: to unify China's seven kingdoms into one magnificent empire
n.2 is acquisition for KPI (Kelab Pencinta Ilmu)
Executive producer, Han Samping, Hiromitsu Furukawa ; writer, Wang Peigong, Chen Kaige
Cast: Gong Li, Zhang Fengyi, Li Xuejian
Keywords: Epic films; Assassination -- China -- Drama